The attitudes of junior college and centralised institute students towards the learning of Tamil as their mother-tongue in Singapore - Premalatha Parasuraman. (2008)
This study is designed to investigate pre - university students' attitudes towards their mother tongue, Tamil. It was aimed at finding out the factors that were significantly related to their attitudes towards the language.